Different oxygenation modalities for early post-extubation: a single center randomized controlled trial - Walid Omar Ahmed; Farouk Mohamed; Yasser Sadek Nassar; Farouk Mostafa Faris (Egyptian Journal of Critical Care Medicine)
Abstract Background Re-intubation after planned extubation from invasive ventilation is frequently encountered in ICU practice and carries a higher incidence of morbidities and mortalities. We aim to compare high-flow nasal cannula (HFNC) to non-invasive ventilation (NIV) and conventional oxygen therapy (COT) immediately post-extubation from MV and to follow the incidence of reintubation and ICU outcomes. Methods This randomized clinical trial was conducted on 60 patients who were divided equally into 3 different groups according to oxygenation strategy after extubation from invasive MV (HFNC, COT, and NIV groups). The primary outcome was the re-intubation rate, while the secondary outcomes were ICU stay and 28-day mortality. Results The mean age of all patients was 62 ± 20 years, 32 were male, and 21 were smokers. Clinical scores (SOFA and APACHE II), and co-morbidities were matched among the three groups. Both HFNC and NIV (4 patients, 20% in each group) were associated with a significantly lower rate of re-intubation than the COT group (10 patients, 50%) with a p-value < 0.05. The COT group (12.2 ± 6 days) is associated with prolonged ICU stay relative to either HFNC or NIV (8.1 ± 3 or 7.5 ± 3.2) with a p-value of 0.04 for both. ICU and 28-day mortalities were not significantly different among the three groups. Conclusion High-flow nasal cannula and non-invasive mechanical ventilation decreased the rate of re-intubation after successful extubation with better oxygenation and lower ICU stay than conventional oxygen therapy. Trial registration Clinicaltrials.gov [NCT04441736].